2020
DOI: 10.1007/s11295-019-1385-y
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an SNP-based high-density genetic map for Japanese plum in a Chinese population using specific length fragment sequencing

Abstract: The Japanese plum (Prunus salicina Lindl.) is one of the most important stone fruit crops in China. High-density linkage map is valuable resources which enhance functional genomics and genetic breeding studies. So far several Japanese plum linkage maps have been reported using different kinds of molecular markers; however, the marker numbers and chromosome coverage are limited. Recently, a newly developed strategy which genome sequencing towards specific-locus amplified fragments (SLAF) markers, has been prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…Because of the lower availability of AFLP, RAPD, RFLP, and SSR markers, the map density was not high enough and the adjacent marker gaps were larger in previous apricot linkage maps ( Lalli et al, 2008 ). SNPs are the most common genetic variation in the whole genome, and they are very important genetic markers for constructing a high-density genetic map, resulting in a significant decrease in the time and cost of genotyping ( Zeballos et al, 2016 ; Zhang et al, 2020 ). Recently, some SNP markers have been used to construct genetic maps in apricots to screen for QTLs related to fruit development period-related traits and graft compatibility ( Salazar et al, 2016 ; Pina et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the lower availability of AFLP, RAPD, RFLP, and SSR markers, the map density was not high enough and the adjacent marker gaps were larger in previous apricot linkage maps ( Lalli et al, 2008 ). SNPs are the most common genetic variation in the whole genome, and they are very important genetic markers for constructing a high-density genetic map, resulting in a significant decrease in the time and cost of genotyping ( Zeballos et al, 2016 ; Zhang et al, 2020 ). Recently, some SNP markers have been used to construct genetic maps in apricots to screen for QTLs related to fruit development period-related traits and graft compatibility ( Salazar et al, 2016 ; Pina et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the published linkage maps, the genetic group constructed in our study covered a longer genetic distance and contained a higher marker density. The differences in the length and density of genetic maps may be related to the genetic distance between the parents, the number of markers, and the population size used in different studies ( Zhang et al, 2020 ). For example, Shi et al (2020) published a peach map including 7,998 SLAF markers covering the peach genome of 1098.79 cM based on an F1 peach population of 202 individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Prunus has shown conserved intraspecific and intragenic collinearity in the Rosaceae family, with the peach being considered a model species for the genus Prunus for multiple types of genetic research (Arús et al 2012;Carrasco et al 2018;Marti et al 2018). Zhang et al (2020) found that the correlation of eight chromosomes was greater than 0.8, indicating a high level of collinearity between the Japanese plum and peach genomes. A recently released plum genome has been published, and collinearity analysis has shown that the assembled genomes of the plum also exhibit a high level of genome synteny with the peach (Liu et al 2020).…”
Section: Discussionmentioning
confidence: 95%
“…NGS is a kind of low-cost technologies to discover large numbers of SNPs for extensive genetic studies, including within-species diversity analysis, linkage map construction, and genome-wide association studies (GWAS), which is allowing significant advances in plant genetics and breeding [6,22,23,29]. The genus Prunus has shown conserved intraspecific and intragenic collinearity in the Rosaceae family, and peach has been considered as a model species for the genus Prunus regarding multiple genetic types of research [30][31][32][33]. On these bases, for the first time, we conducted high-depth (~20×) whole-genome resequencing of 67 plum accessions using the peach genome sequence as a reference, obtaining an average of 6.9 Gb high-quality data for each acquisition, which ensured the accurate and comprehensive population genetic analysis.…”
Section: Discussionmentioning
confidence: 99%